Focal Cortical Dysplasia in Pediatric Epilepsy - Sun Ah Choi; Ki Joong Kim (Korean Child Neurology Society, 2019)
Focal cortical dysplasia (FCD) is the most common cause of intractable focal epilepsy in children undergoing epilepsy surgery. In these patients, seizures usually develop in early childhood and are often explosive from their onset. This review summarizes the classification of FCD and provides recent updates, clinical features, and illustrative electrophysiological and neuroimaging findings, which are expected to help physicians better understand FCD. Children with intractable focal epilepsy should receive timely evaluations for epilepsy surgery. Complete resection of the epileptogenic zone and an early surgical intervention lead to favorable surgical outcomes.